Aggression and violence against health care workers in Germany - a cross sectional retrospective survey - Kuhnert Saskia; Schablon Anja; Zeh Annett; Franz Simone; Nienhaus Albert (BMC, 2010)
Abstract Background Although international scientific research on health issues has been dealing with the problem of aggression and violence towards those employed in health care, research activities in Germany are still at an early stage. In view of this, the aim of this study was to examine the frequency and consequences of aggressive behaviour towards nurses and health care workers in different health sectors in Germany and to assess the need for preventive measures. Methods We conducted a cross-sectional retrospective survey. Nurses and health care workers from two nursing homes, a psychiatric clinic and a workshop for people with disabilities were interviewed using a standardised questionnaire. The sample covered 123 individuals (response rate 38.8%). The survey assessed the frequency, the type and the consequences of aggressive behaviour, and social support in connection with coping with aggression in the workplace. Odds ratios (OR) and 95% confidence intervals (CI) for putative risk factors which may influence the stress induced by aggression at the workplace were calculated using conditional logistic regression. Results During the previous twelve months 70.7% of the respondents experienced physical and 89.4% verbal aggression. Physical aggression more frequently occurred in nursing homes (83.9% of the employees) and verbal aggression was more common in the psychiatric clinic (96.7% of the employees). The proportion of the individuals affected in the workshop for people with disabilities was lower (41.9% and 77.4% respectively). The incidents impaired the physical (55%) and emotional well-being (77.2%) of the employees. The frequency of incidents (weekly: OR 2.7; 95% CI 1.1-6.4) combined with the lack of social support (OR 2.8; 95% CI 1.2-6.6) increased the probability of higher stress due to aggression. Conclusions This study corroborates previous reports of frequent physical and verbal aggression towards care workers in the various areas of health care. The present study highlights differences between various areas of health care in Germany and the aggravating effect of prevention neglect such as missing social support at the workplace. Therefore our data suggest the need for improved target group specific prevention of aggressive incidents towards care workers and the need for effective aftercare in Germany.